PENDAMPINGAN PEMETAAN POTENSI DESA DONO ARUM BERBASIS ASSET BASED COMMUNITY DEVELOPMENT GUNA MEWUJUDKAN DESA WISATA YANG BERKARAKTER DAN SMART VILLAGE - Ifaty Fadliliana Sari; Dewi Ayu Hidayati; Yuni Ratnasari; Siti Habibah (Jurnal Abdi Insani, 2022)
Village development is one of the main focuses of national development in line with the Nawacita program and the Village SDGs. In order to make villages independent, the government provides village funds that can be used for village progress. Every village has potential that can be developed optimally. Efforts are needed to identify the potential of the village as a whole. Therefore, the organization of this activity aims to increase the insight and capacity of the community in identifying the potential of an asset-based village or village based on community development in Dono Arum village, Seputih Agung District, Central Lampung Regency. Activities include training, focus group discussions (FGD), and assistance in identifying village potential and increasing institutional or community capacity. The method used in this service activity is the state analysis stage, object intervention, and evaluation or reflection. In particular, this community service activity has provided an overview to the local community on how to properly and correctly map village potentials. Provide an understanding of smart village-based village development. In addition, this activity refers to several achievements, including; the formation of a joint commitment between village government officials, institutions, and the community to focus on village development in the three potentials that characterize Dono Arum Village. The potentials that are the main focus include (1) the potential for natural resources, (2) the potential for human resources and technology, and (3) the tourism potential. This community empowerment activity has provided understanding and increased the capacity of the Dono Arum village community in mapping the potential of an asset-based village with a 4% increase in knowledge percentage.